Dampak Program Bantuan PKL Terhadap Tingkat Motivasi Pedagang Kaki Lima (PKL) di Provinsi Sumatera Barat - Saili, Drs. Syamsir, M.Si (TINGKAP, 2011)
ABSTRACT The objectives of this study are 1) to describe the level of motivation Retailers/Peddlers in West Sumatera in running their bussiness as a Retailer/Peddler and 2) to identify the impact of Loan for Retailer program toward the retailersâ€™ motivation in running their bussiness as a Retailer/Peddler. This study was conducted in three regions of cities in the area of West Sumatera province, namely Padangpanjang, Bukittinggi, and Payakumbuh. A qualitative method through field study was used in this study. Data were collected though structured and depth-interview, observation, questionnaire, and study of documentation. There are 434 Retailers/Peddlers covered in this study. Quantitative data from questionnaire were analyzed with frequency and percentage while qualitative data from informants and observation were analyzed through the model of interactive analysis. The finding of this study indicated that the loan for retailer program did not have so significant impact for increasing motivation of the retailers/peddlers in running their bussiness. Â  Kata Kunci: Program Bantuan PKL, Pedagang Kaki Lima (PKL), Program Registrasi PKL, Motivasi